2021
DOI: 10.1002/cssc.202100196
|View full text |Cite
|
Sign up to set email alerts
|

H2‐free Plastic Conversion: Converting PET back to BTX by Unlocking Hidden Hydrogen

Abstract: The strong desire for a circular economy makes obtaining fuels and chemicals via plastic degradation an important research topic in the 21st century. Here, the first example of the H 2 -free polyethylene terephthalate (PET) conversion to BTX (benzene, toluene and xylene) was achieved by unlocking hidden hydrogen in the ethylene glycol part over Ru/Nb 2 O 5 catalyst. Among the whole process (hydrolysis, reforming and hydrogenolysis/ decarboxylation), the parallel hydrogenolysis and decarboxylation were competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…More complex phosphine ligands have also been tested, but the economic viability on an industrial scale seems to be rather limited [147] (Table 1, entries 2-3). Two very important studies have been published on the efficient conversion of postconsumer PET to benzene, toluene, and xylenes by reportedly "unlocking hidden hydrogen in the ethylene glycol part" with Ru/Nb 2 O 5 catalyst [156,157]. The hydrogen is formed in situ during the reaction from ethylene glycol, and it appears that, in the presence of Ru/Nb 2 O 5 , two different pathways (decarboxylation and hydrogenolysis) compete to determine the selectivity toward alkyl-aromatic compounds (Table 1, entries 4-5) [156].…”
Section: Hydrogenolysismentioning
confidence: 99%
“…More complex phosphine ligands have also been tested, but the economic viability on an industrial scale seems to be rather limited [147] (Table 1, entries 2-3). Two very important studies have been published on the efficient conversion of postconsumer PET to benzene, toluene, and xylenes by reportedly "unlocking hidden hydrogen in the ethylene glycol part" with Ru/Nb 2 O 5 catalyst [156,157]. The hydrogen is formed in situ during the reaction from ethylene glycol, and it appears that, in the presence of Ru/Nb 2 O 5 , two different pathways (decarboxylation and hydrogenolysis) compete to determine the selectivity toward alkyl-aromatic compounds (Table 1, entries 4-5) [156].…”
Section: Hydrogenolysismentioning
confidence: 99%
“…From the perspective of chemical bond activation and cleavage, Wang et al fabricated a multifunctional Ru/Nb 2 O 5 catalyst to break CÀ O and CÀ C bonds in various aromatic waste plastics (e. g., PET, PPO, PS, and PC) for the production of monocyclic arenes by hydrogenolysis. [39] The hydrogen species is either from external added H 2 or from the reforming of the ethylene glycol units in PET. [39a] Main products obtained over Pd/Nb 2 O 5 and Pt/Nb 2 O 5 were saturated ring products due to the strong hydrogenation ability of Pd and Pt (Figure 6a).…”
Section: Degradation Of Waste Plastics Into Value-added Liquid Fuels and Waxesmentioning
confidence: 99%
“…With the assistance of the hydrogen species dissociated from the small particle Ru, the precise activation and cleavage of CÀ O and CÀ C bond within aromatic plastics is achieved (Figure 6d). [39] Interestingly, it was found that Ru/Nb 2 O 5 also exhibited poor decarboxylation performance than Ru/NiAl 2 O 4 , because the strong interaction between Ru and Nb 2 O 5 results in the presence of more positively charged Ru species (Figure 6c), restricting the undesired decarboxylation reaction. [39a] The Ru/ Nb 2 O 5 catalyst can not only convert a single aromatic plastic, but also realize the direct conversion of mixed aromatic plastics into arenes with high selectivity, resulting in aromatic yields as high as 75-85 % (Figure 6e).…”
Section: Degradation Of Waste Plastics Into Value-added Liquid Fuels and Waxesmentioning
confidence: 99%
“…The Ru/Nb 2 O 5 system enables a selective and effective way for the chemical upcycling of waste aromatic plastics into the valuable arenes contributing to the future establishment of the circular plastic economy. Afterwards, Wang and co-workers developed a H 2 -free route to convert PET into BTX (benzene, toluene, xylene) products in water by using the Ru/Nb 2 O 5 catalyst, [42] in which the reaction of hydrolysis [the H 2 needed originated from the ethylene glycol (EG) intermediate], reforming and hydrogenolysis/decarboxylation happened, adding new options in the circular economy of PET.…”
Section: Hydrogenolysismentioning
confidence: 99%